PTU-116 Exploring the Association between Genetic Polymorphisms and Swallowing Motor Cortex Excitability Induced by Repetitive Transcranial Magnetic Stimulation: Is Response Predicted by Genetic Predisposition?. (17th August 2016) - Raginis-Zborowska, A; Hamdy, S; Michou, E; Pendleton, N
Abstract : Introduction: Non-invasive brain stimulation such as repetitive Transcranial Magnetic Stimulation (rTMS) is used to manipulate excitability in the swallowing motor cortex. However, the molecular mechanisms controlling this excitability remain unknown. Swallowing neurophysiology and impairments might be in part driven by genes. The aim of this study was to determine whether the variability in excitability after 1 Hz and 5 Hz rTMS within the pharyngeal motor cortex might be affected by putative selected single nucleotide polymorphisms (SNPs). Methods: 11 SNPs from 7 genes ( BDNF, COMT, TRKB, APOE, DRD2, GRIN2B and GRIN1 ) were selected a priori to explore possible link between neurophysiological outcomes after rTMS intervention with high (5 Hz) and low (1 Hz) frequencies. A total of 41 healthy young (mean age 25.4 ± 4.6 years) volunteers were investigated. All subjects were assessed for corticobulbar excitability after single-pulse TMS. Repeated measurements of motor evoked potentials (MEPs) from the pharynx were recorded before and for up to one hour after the interventions of 1 Hz and 5 Hz rTMS. Salivary DNA was collected and process post-hoc and SNPs correlated with pharyngeal MEPs and interventions (1 vs. 5 Hz rTMS). Results: Non-carriers of the minor G allele from SNP rs6269 from COMT gene are more likely to be non-responders ( P -value =0.026), while those carrying G allele are more likely have inhibitory and excitatory outcomes after delivering 1 Hz and 5 Hz rTMS. Cross-tabulation analysis with chi square indicated there was a significant difference between 5 Hz rTMS outcome and one SNP - DRD2 rs1800497: specifically carriers of minor allele A from this DRD2 gene were more strongly inhibited ( P -value =0.03) while non-carriers were more likely to represent non-responders. Conclusion: We now report possible evidence for genetic associations with the neuromuscular control of swallowing influenced by rTMS paradigms. Two SNPs from COMT and DRD2 genes appear to play a role in pharyngeal cortex excitability depending on the stimulation applied. Further research is needed to establish more detailed information which might be used in developing more stratified approach in the field of dysphagia therapy with non-invasive brain stimulation. Disclosure of Interest: None Declared